A Study of the Key Success Factors of Franchises in Malaysia - Lim, Genevieve Louise Santiago (2004)
The Malaysian franchise industry is still considered relatively young compared to other developed countries in the world. It was only in the early 1990s that its growth started when the Government began encouraging the industry to play an important role in fostering entrepreneurship in the country. Franchising in Malaysia has great potential. In fact, over the last ten years, the industry is able to maintain an average growth rate of around 10% per annum. Its annual turnover for the period 2001-2002 recorded a huge increase of 24% with a turnover of RM 10.7 billion for the year 2002 compared to RM 8.6 billion in the year 2001. Despite the high turnover, the industry still only accounted for 5% of the local retail sales and contributed only about 12% to the country’s gross domestic product.The Government is serious in its effort to make franchising one of the most viable methods of business creation and expansion in Malaysia. Anticipating its rapid growth, the Government introduced and passed the Malaysian Franchise Act 1998 that aims to regulate the industry. Furthermore, the 8th Malaysian Plan under the former Prime Minister Tun Dr. Mahathir Mohammad includes initiative to develop 1,000 franchisees and 50 franchisors from 2001 to 2005 through the allocation of RM 200 million into the Fund for Development and Promotion (FDP) of Malaysia Brands. Financial schemes are also provided under the Franchise Development Program that includes support like the Franchise Financing Scheme (FFS) and the Franchise Development Scheme (FDS). Besides government support, the existence of the Malaysian Franchise Association (MFA) also boosts the level of success of the industry. Acting as liaisons among its members, the Government, and the international business world, the MFA has a vision to make Malaysia the franchise growth center in Asia one day. With all the above in place, are they sufficient to make any business or franchise work? Are there other factors, inherent within the franchise itself, which contribute to the success or failure of a venture? Therefore, the research objective of this paper is to identify the key success factors that enable franchises to sustain their operations in Malaysia. Using the actual experiences of ten different firms involved in franchising, hypotheses will be tested in order to come up with a final central research proposition to answer the central research question presented as: why are some franchises operating in Malaysia successful? Five basic key success factors will be studied, namely, product / service concept, business system, support system, people, and adaptation.